The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1475-2875-11-390
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of diagnostic for malaria in Extra-Amazon Region, Brazil

Abstract: BackgroundRapid diagnostic tests (RDT) for malaria have been demonstrated to be effective and they should replace microscopy in certain areas.MethodThe cost-effectiveness of five RDT and thick smear microscopy was estimated and compared. Data were collected on Brazilian Extra-Amazon Region. Data sources included the National Malaria Control Programme of the Ministry of Health, the National Healthcare System reimbursement table, laboratory suppliers and scientific literature. The perspective was that of the Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 32 publications
1
27
0
2
Order By: Relevance
“…In the research protocol “economic decision models for genomic testing strategies”, Peters et al (2015) commented that it is rare for economic studies to provide suitable information about the methods used to evaluate how the evidence was identified 7 . A similar situation was observed in this review, since only two of the 12 articles on cost-effectiveness that were reviewed actually described the evaluation process used to determine the quality of the primary studies 44 , 53 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the research protocol “economic decision models for genomic testing strategies”, Peters et al (2015) commented that it is rare for economic studies to provide suitable information about the methods used to evaluate how the evidence was identified 7 . A similar situation was observed in this review, since only two of the 12 articles on cost-effectiveness that were reviewed actually described the evaluation process used to determine the quality of the primary studies 44 , 53 .…”
Section: Discussionsupporting
confidence: 55%
“…The only CUA, which used DALY as an outcome, applied the estimates of sensitivity and specificity as epidemiological parameters in the decision model and the variations in these measures in the sensitivity analysis. Two studies (17%) referred to the application of methods defined in the literature to check the quality of the accuracy studies that underpinned the economic model 44 , 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Decision-makers are being faced with increasingly difficult decisions when they consider the addition of new technologies to national malaria control program [ 28 ]. Aiming to help in decision-making, various economic studies have examined aspects related to primary prevention, diagnosis and treatment of malaria, with emphasis on vaccines [ 29 , 30 ], mosquito nets impregnated with insecticides [ 31 , 32 ], mass screening followed by treatment [ 33 ], use of RDTs to diagnose the infection [ 34 , 35 ] and the use of schemes for chemo-prophylaxis and treatment [ 36 38 ]. Although there are no published studies on cost-effectiveness for G6PDd diagnosis in connection with malaria, recent publications have discussed the urgency of evaluating the efficiency of RDTs used to detect G6PDd so as to guarantee safety in the treatment of these patients [ 11 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies were not identified in the literature that evaluate the cost of G6PDd in the context under research, there are recent publications that indicate how urgent it is to carry out economic evaluations on this topic, highlighting especially the need to estimate the costs and effectiveness of incorporating rapid diagnostic tests (RDTs) to detect G6PDd. These should be used at the point of care before applying PQ [ 4 , 6 , 46 ], similar to what has been described in the Brazilian context in relation to the cost-effectiveness of RDTs for diagnosing malaria itself [ 30 , 47 ], helping in decision-making on the incorporation or not of this technology. Currently, two RDTs to detect G6PDd in field conditions (BinaxNOW® G6PD and CareStartTM G6PD) have been evaluated in malaria endemic areas [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%